Distribution of radionuclides in an iron calibration standard for a free release measurement facility. (March 2016) - Hult, Mikael; Stroh, Heiko; Marissens, Gerd; Tzika, Faidra; Lutter, Guillaume; Šurán, Jiri; Kovar, Petr; Skala, Lukas; Sud, Jaromír
Abstract: A Europallet-sized calibration standard composed of 12 grey cast iron tubes contaminated with 60 Co and 110m Ag with a mass of 246 kg was developed. As the tubes were produced through centrifugal casting it was of particular concern to study the distribution of radionuclides in the radial direction of the tubes. This was done by removing 72 small samples (swarf) of ~0.3 g each on both the inside and outside of the tubes. All of the samples were measured in the underground laboratory HADES. Highlights: A 246-kg reference standard for a free release measurement facility is described. The distribution of 110m Ag and 60 Co inside each of 12 iron tubes was measured. Silver-110m was homogeneously distributed along the main axis of the tubes. There was 3% higher concentration of 110m Ag on the inside of each tube. Cobalt-60 was homogeneously distributed both in radial and axial directions.